Active Solutions for Accelerated Tahfidz Class Management in Al-Qur'an Learning at Muhammadiyah Gumantar Islamic School - Herlianti, Aprilia; Nisa, Choirun (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to describe the implementation of classroom management in the Tahfidz acceleration program for Al-Qur'an learning at MI Muhammadiyah Gumantar, Klaten. Methodology: The research focuses on teaching methods, teacher strategies in managing the class, challenges encountered, and active solutions applied. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation involving the principal, Tahfidz teachers, and students in the accelerated class. Data validity was ensured through source and technique triangulation.Results: The results of the study show that the talaqqi, ziyadah, and muroja'ah methods are applied in a structured manner through classroom management strategies that emphasize small group division, motivation reinforcement, and effective time management. Challenges arise in relation to variations in student concentration and suboptimal learning support at home. This study offers an original contribution in the form of an adaptive classroom management model that can be applied to accelerated tahfidz programs in Islamic schools.Applications/Originality/Value: These findings have practical value for the development of Islamic education practices, particularly in improving the effectiveness of tahfidz learning through classroom management that is responsive to student needs.